Managing and sharing research data : a guide to good practice - Corti, Louise; Eynden, Veerle van den; Bishop, Libby; Woollard, Matthew (Los Angeles : SAGE, 2014)
This text looks explicitly at data management and sharing, providing readers with the skill-set needed to successfully produce high quality research assets.
The importance of managing and sharing research data -- The research data lifecycle -- Research data management planning -- Documenting and providing context for data -- Formatting and organizing data -- Storing and transferring data -- Legal and ethical issues in sharing data -- Rights relating to research data -- Collaborative research : data management strategies for research teams and research managers -- Making use of other people's research data : opportunities and limitations -- Publishing and citing research data.
Companion website with additional exercises and links from the UK Data Service available at: http://ukdataservice.ac.uk/manage-data/handbook
Includes bibliographical references and index.
Keywords: Social sciences -- Research; Communication in the social sciences; Intellectual cooperation; Database management; Research -- Data processing